ANALYSIS ALTMAN Z-SCORE TO PREDICT BANKRUPTCY IN PT RAMAYANA LESTARI SENTOSA TBK - Lestari, Dwi; Surbakti, Lidya Primta (Epigram, 2024)
The objective of this study is to ascertain the anticipated level of bankruptcy risk at PT Ramayana Lestari Sentosa, Tbk, based on the annual financial reports spanning from 2018 to 2020. The data utilized in this analysis comprise the Financial Statements of PT Ramayana Lestari Sentosa, Tbk for the specified period, accessible through the official website of the Indonesia Stock Exchange, www.idx.com. As PT Ramayana Lestari Sentosa, Tbk is a publicly traded retail company in Indonesia, its financial statements are publicly accessible. The technical analysis employed in this research utilizes the Altman Z-score method, entailing calculations based on the Altman Z-Score formula. The Z-Score calculation for 2018 yielded a result of 6.271, indicating placement within the safe zone. In 2019, it slightly decreased to 6.190, still within the safe zone. Subsequently, in 2020, it experienced a slight increase to 6.211. The Z-Score results for the period spanning 2018 to 2020 suggest that PT Ramayana Lestari Sentosa, Tbk can be classified as a financially healthy company with no evident potential for bankruptcy. However, considering the advancing technology and evolving consumer behaviors, the company may face bankruptcy risks if it fails to adapt and expand its operations into e-commerce platforms.